Managing Digital Nomads Meet Remote Workers: A Qualitative Research in Seven International Organizations - Joana FERNANDES; Ana Cláudia RODRIGUES (Communications of International Proceedings, 2024)
Although the studies on digital nomadism increased in the last years, there aren’t many who explore the management perspective on this type of labour. The main objective of this study is to define the human resources management strategy applied to digital nomads and understand the common topics of managing other remote workers. Using Grounded Theory approach, we conducted seven semi structured interviews in two rounds of interviews to various types of professionals from companies that hire digital nomads and fully remote workers. Findings show that the human resources management strategy can be divided in organizational, human resources department and team management. Furthermore, findings show that fully remote workers and digital nomads are managed the same way. This paper offers a model synthetizing the main issues of managing digital nomads. Limitations and suggestions to future studies are also mentioned.
Keywords: digital nomads; remote workers; management strategy; human resources